Osteometric Sex Determination of Burned Human Skeletal Remains - Gonçalves, David (2013)
Sex determination of human burned skeletal remains is extremely hard to achieve because of heat-related fragmentation, warping and dimensional changes. In particular, the latter is impeditive of osteometric analyses that are based on references developed on unburned bones. New osteometric references were thus obtained which allow for more reliable sex determinations. The calcined remains of cremated Portuguese individuals were examined and specific standard measurements of the humerus, femur, talus and calcaneus were recorded. This allowed for the compilation of new sex discriminating osteometric references which were then tested on independent samples with good results. Both the use of simple section points and of logistic regression equations provided successful sex classification scores. These references may now be used for the sex determination of burned skeletons. Its reliability is highest for contemporary Portuguese remains but nonetheless these results have important repercussion for forensic research. More conservative use of these references may also prove valuable for other populations as well as for archaeological research.